Percutaneous A1 pulley with corticosteroid injection for trigger finger release: a systematic review - Jimmy Wen; Burhaan Syed; Ramy Khalil; Mouhamad Shehabat; Meraj Alam; Romteen Sedighi; Daniel Razick; Muzammil Akhtar; Adam Razick; Foad Elahi (Journal of Orthopaedic Surgery and Research)
Abstract Background Corticosteroid injection (CI) is one of the first-line treatments for trigger finger (TF) before escalation to surgical procedures such as percutaneous A1 pulley (PAP) release. This systematic review compares outcomes of concurrent PAP and CI for trigger finger release (TFR). Methods A systematic search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted in PubMed, Embase, and Cochrane Library. Study variables included the number of patients, mean age, mean follow-up, affected finger, Quinnell grading, return to activity, pre-and post-operative patient-reported outcomes (PROs), and complications. Results Seven studies were included, with 685 patients with a mean age of 52.0 years (range of 38.0 to 58.9) and a mean follow-up time of 22 weeks (range 1 week to 52 weeks). Throughout these studies, PAP and CI were performed on 243 thumbs, 115 index fingers, 189 middle fingers, 138 ring fingers, and 10 small fingers. PAP and CI reported satisfaction and pain resolution for 96.2% (five studies) of patients. Additionally, all patients returned to activity, sports, or work (three studies). Conclusion Concurrent PAP and CI positively affect clinical outcomes, PROs, and is a well-tolerated procedure with a low rate of complications.